Memories on the Wall. Wall Maturity in Ana Langeheldt - Navarro Morcillo, Pablo (Nawi, 2022)
When classifying Ana Langeheldt’s artwork (Seville, 1978), it is essential to mention its multidisciplinary nature, interchangeably alternating between painting, illustration and collage within street study or practice. This paper focuses focus on the facet carried out in public spaces, where the artist has performed art pieces ranging from graffiti to commissioned urban art, the latter being the field where she has been performing some interesting productions that reveal the maturity obtained after a two-decade career. This paper draws a portrait from her beginnings in graffiti, before centering on the evolution that can be seen on her latest commissioned wall work, since 2018.